2019
DOI: 10.1002/cite.201800184
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Membrane Reactors for Integrated Coupling of Oxidative and Thermal Dehydrogenation of Propane

Abstract: This study presents strategies capable to intensify the thermal dehydrogenation of propane (TDH) using integrated reactor concepts. An inert packed bed membrane reactor for distributed dosing of oxygen to realize the oxidative dehydrogenation (ODH) was studied and compared to a reactor with catalytically active membrane. The latter concept allows to combine TDH and ODH in one apparatus to overcome the chemical equilibrium by in situ conversion of the by‐product H2 using O2 or in a reverse water‐gas shift react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 29 publications
0
19
0
6
Order By: Relevance
“…Model-based simulation studies of integrated membrane reactor concepts of various complexity for the oxidative dehydrogenation of propane to propene J. P. Walter 1) (E-Mail: jan.walter@ovgu.de), A. Brune 1,2) , Prof. A. Seidel-Morgenstern 1,3) , Prof. C. Hamel 1,2) 1) Otto-von-Guericke-University, Chemical Process Engineering, Universitä tsplatz 2, 39106 Magdeburg, Germany The role of oxidative propane dehydrogenation (ODH) is of interest as a promising alternative to the thermal propane dehydrogenation process (TDH) [1]. The major drawback of the TDH is a rapid catalyst coking, which can be repressed in the ODH because of the present oxygen.…”
Section: P1348 Reaktionstechnikmentioning
confidence: 99%
See 3 more Smart Citations
“…Model-based simulation studies of integrated membrane reactor concepts of various complexity for the oxidative dehydrogenation of propane to propene J. P. Walter 1) (E-Mail: jan.walter@ovgu.de), A. Brune 1,2) , Prof. A. Seidel-Morgenstern 1,3) , Prof. C. Hamel 1,2) 1) Otto-von-Guericke-University, Chemical Process Engineering, Universitä tsplatz 2, 39106 Magdeburg, Germany The role of oxidative propane dehydrogenation (ODH) is of interest as a promising alternative to the thermal propane dehydrogenation process (TDH) [1]. The major drawback of the TDH is a rapid catalyst coking, which can be repressed in the ODH because of the present oxygen.…”
Section: P1348 Reaktionstechnikmentioning
confidence: 99%
“…2017, 89, 1159-1173. DOI: 10.1002 It has been shown that H 2 -to-O 2 ratios up to 2 are beneficial for the oxidation path of the H 2 O 2 direct synthesis using supported Pd-catalysts [1]. So far, a re-saturation setup has been studied, using continuous-flow catalysis to contact the reaction gases with the catalyst suspended in the liquid phase.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[181] To address the heat demand by alkane dehydrogenation, Brune et al proposed a hybrid system, in which endothermic dehydrogenation reactions and the exothermic O 2 -ODH reactions are conducted on different sides of a membrane, to make the overall process thermal-neutral. [182]…”
mentioning
confidence: 99%